Edukasi Gizi Seimbang dan Hubungannya dengan Penyakit Degeneratif pada Lansia - Nathasa Weisdania Sihite; Manuntun Rotua (Unika Santu Paulus Ruteng, 2022)
Lifestyle about balanced nutrition dramatically affects the health status and life expectancy of the elderly. This community service activity aims to provide basic knowledge and skills to the elderly about the importance of balanced nutrition and its relation to degenerative diseases that often suffer the elderly. The service was carried out at the auditorium of the Pentecostal Church in Indonesia (GPDI) Segaran Palembang. A team of lecturers carried out the method of activity by providing material in the form of lectures, discussions, and video screenings. Based on the frequency distribution results of the number of participants who attended, it was found that many older people had degenerative diseases such as hypertension and obesity (overweight). The community service activities carried out were welcomed by the participants. This was seen by a large number of participants present, the enthusiasm of the participants in preparing a balanced nutrition menu and actively participating in discussion activities on balanced nutrition. Education and counselling are vital to do for the elderly. This will increase their knowledge of the elderly about balanced nutrition guidelines that can be used to prevent and overcome the problem of degenerative diseases in old age. For both private and government agencies, it is necessary to be more prompt in providing continuous counseling regarding dietary regulation, especially for the elderly with a history of degenerative diseases.